PERAN IUCN MENGELUARKAN BBRRS DARI DAFTAR WORLD HERITAGE IN DANGER TAHUN 2009-2018 - Devi, Ni Made Mahatma; Priadarsini, Ni Wayan Rainy; Nugraha, A.A Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT International Non Governmental Organization (INGO) is one of the subjects of discussion in International Relations. The International Union for Conservation of Nature (IUCN) as an Advisory Board collects natural sites that are nominated for World Heritage status, manages complementary sites, and contributes to supporting the implementation of World Heritage. One of the sites in the spotlight is the Belize Barrier Reef Reserve System (BBRRS), which is a natural site that has been designated as a World Heritage List in Danger since 2009. BBRRS was threatened by the increasing of activities in the tourism, fisheries and oil mining sectors. The IUCN as an Advisory Board during 2009-2018 had an important role in the process of erasing BBRRS from the List of World Heritage in Danger. This descriptive qualitative study uses the literature method to describe the role of international organizations in influencing the focus and decisions of international forums. Keywords: IUCN, World Heritage in Danger, Belize Barrier Reef Reserver System, Advisory Body